Subungual myxoid neurothekeoma of the toe: A rare entity - Banushree C Srinivasamurthy; Ramchandra V Bhat (Wolters Kluwer Medknow Publications, 2020)
Myxoid neurothekeomas are rare benign soft-tissue tumors that are considered to be of the nerve sheath origin. They usually occur in young most commonly on the upper extremities, head, and neck, with a predilection for the female population. Based on histomorphological appearance and immunohistochemical findings, there are three variants of neurothekeoma myxoid, cellular, and mixed type. The myxoid type is characterized by a greater degree of myxomatous changes, less cellularity with well-circumscribed spindle cells in the myxoid matrix, and stain positively for S-100. This has to be differentiated from several myxoid soft-tissue tumors. We present a rare case of myxoid neurothekeoma occurring in elderly females in the toe of the lower extremity.